WORKSHOP TERAPI ISOMETRIC HANDGRIP TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI - Dian Anggri Yanti; Syatriawati Suhaimi; Iskandar Markus; Junita Ika Br Ginting; Dila Rizkia (JURNAL PENGMAS KESTRA (JPK), 2021)
Hypertension is a condition when the systolic blood pressure (BP) is greater than 140 mmHg and the diastolic blood pressure is greater than or above 90 mmHg. The American Heart Association (AHA), the American population aged over 20 years suffering from hypertension has reached 74.5 million people, but almost 90-95% of cases have no known cause. Hypertension is likely to cause fatal complications and opens greater opportunities for sufferers. to suffer a stroke, coronary heart disease, high risk of kidney failure, heart failure, and eye damage. Physical activity that can be used to lower blood pressure is the Isometric Handgrip Exercise which is done with static exercises on contracting muscles, without any change in muscle length or hand joint movement. Objective: This activity aims to determine the effect of isometric handgrip therapy on blood pressure in patients with hypertension in the working area of ​​the Batang Kuis Health Center. Methods: The method used in this activity is in the form of socialization of health education related to the effect of isometric handgrip therapy on blood pressure in patients with hypertension. Results: Based on the results of observations from the socialization carried out, it proved that there was an effect of giving isometric handrip therapy on reducing blood pressure in patients with hypertension in the work area of ​​the Batang Kuis Health Center. Suggestion: Therefore, it is hoped that this activity will provide information and increase knowledge for patients and nursing services at the Batang Kuis Health Center.